Analysis of Employer Branding towards Relationship Manager Priority Banking and SME Banking in Standard Chatered Bank - Pratama, Ryan Aditya; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2013)
Talent is scarce, companies fight for top performer to growth and sustain the business. To attract talent, employer branding is the sexiest strategy that man companies currently attempt to do. Employer branding is a strategy that company implement to create best place to work perception on employees mind. It design the long term strategy to manage potential and current employee perception to recruit and retain its top performer. Create Ã‚Â a distinct employer brand is now on the top ofÃ‚Â  the list of priorities for most of key organization. (Collins,2001) Employer branding is a targeted, long-term strategy to manage the awareness and perception of employees, potential employees and related stakeholder with regards to particular firm (Backous& Tikoo,2004). If marketing build brand to attract consumer, employer branding is designed to attract its potential and current talent. The approach is similar but the tool required is difference. Standard Chartered Bank is banking company that operates in 160 country across the world, one of operating country is Indonesia. This company had several award that could be trigger aspiration of job seeker (Vault.inc,2013) in US, Europe and Asia. The challenge that company face is get an achievement to choose as the best place to work in several famous ranking companies in the world such as Fortune, Linkedin, and Inc.com, etc. This is the result of increasing people concern on environment, also banking is now considered had a declining profit. Based on the two facts explain above, it is interesting to explore more on branding strategy on human resource world, and also to understand the correlation with Employee Value Proposition with Total Rewards Framework. The result of this quantitative research is based on random sampling towards 133 respondents in Standard Chartered Bank Indonesia conducted on 1st -9th May 2013. TheyÃ¢â‚¬â„¢re two concept that had an impact on employer branding, first is Employee Value Proposition that had 3 big component which is Employer Value, Employer Distinctive Strength, and Commitment combined with Total Rewards that had 23 key variable component. Whilst to measure impact towards Employer Branding, Regression Analysis test used. The result of Regression Analysis test will indicate thereÃ¢â‚¬â„¢s impact of Employee Value Proposition and Total Rewards towards Employer Branding. Vice versa, there is no significant impact among Employee Value Proposition and Total Rewards with Employer Branding.The discussion on the finding can be very profound. It provides many useful information for future employer branding development. However, the developmentÃ‚Â  of employer brand has to be part of strategic company plan and get fully support from the senior management. This employer branding research study is only beginningÃ‚Â  of very exciting explorative study that can be conducted on the new field that connect human resources, marketing communication and corporate affair. Understand the important of this field, it can be conclude that this field will be continuously evolving and widely implement by companies in the future.Ã‚Â Keywords: Brand, Branding, Employer Branding, Employee Value Proposition, and Total RewardsÃ‚Â